2008
DOI: 10.1111/j.1567-1364.2008.00386.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofKlGUT2, a gene of the glycerol-3-phosphate shuttle, inKluyveromyces lactis

Abstract: KlGUT2 encodes the mitochondrial component of the glycerol-3-phosphate shuttle in Kluyveromyces lactis, a dehydrogenase involved in the maintenance of the NADH redox balance and in glycerol utilization. Deletion of KlGUT2 led to glycerol accumulation during growth in glucose and growth retardation in ethanol. In addition, KlGUT2 deletion altered the expression of other mitochondrial dehydrogenases that contribute to the maintenance of the intracellular redox balance, suggesting a rerouting of ethanol oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Produced glycerol was consumed at a latter stage of the cultivation. The observation of glycerol consumption in this study is borne out by a previous work, which showed that the aerobic assimilation of accumulated glycerol in culture by K. lactis NBRC 1903 cells was due to the activity of glycerol 3-phosphate shuttle [23].…”
Section: Resultsmentioning
confidence: 71%
“…Produced glycerol was consumed at a latter stage of the cultivation. The observation of glycerol consumption in this study is borne out by a previous work, which showed that the aerobic assimilation of accumulated glycerol in culture by K. lactis NBRC 1903 cells was due to the activity of glycerol 3-phosphate shuttle [23].…”
Section: Resultsmentioning
confidence: 71%
“…An earlier publication had also reported this phenomenon for Kluyveromyces. 31 Figure and remained almost constant at (k L a) 0 higher than 23.9 h −1 . Very similar results were obtained in studies of the production of red shikonin pigments by plant cell culture of Lithospermum erythrorhizon 33 and production of biomass of tobacco cells.…”
Section: Resultsmentioning
confidence: 80%
“…The observation of glycerol consumption in Run 1 is borne out by a previous work, which showed that the aerobic assimilation of accumulated glycerol in culture by K. lactis NBRC 1903 cells was due to the activity of glycerol 3-phosphate shuttle. 31 The change in (k L a) 0 resulted in a marked difference in the distribution of metabolic products. The outcome of aeration at higher (k L a) 0 was the distribution of higher X, c A and c Gly , and lower c E .…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, the glycolytic and the PPP accumulated NADH and NADPH in the cytosol. The reduced cofactors are then transferred to the respiratory chain, by the ethanol/acetaldehyde and glycerol-3-phosphate shuttles (27,33,34) and the transdehydrogenase KlNde1 (35,37), where they are reoxidized (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…This plasmid was also used for cloning and overexpression of genes amplified by PCR from the K. lactis genome. The primers used for the amplification of KlALD4, KlALD6, and KlGPD1 and for the construction of the chimeric KlZWF1GFP genes are reported in Table 1, while those for KlGUT2, KlNDE1, and KlNDI1 have been reported elsewhere (34,35). KlZWF1GFP was constructed by amplifying the 5= portion (980 bp of the promoter plus the entire KlZWF1 open reading frame [ORF] without the stop codon) and the 3= portion (stop codon and 640 bp of the 3=-untranslated sequence) of KlZWF1 from pTZ19/ KlZWF1.…”
Section: Methodsmentioning
confidence: 99%